2015
DOI: 10.1080/02640414.2015.1076166
|View full text |Cite
|
Sign up to set email alerts
|

Are the new starting block facilities beneficial for backstroke start performance?

Abstract: We aimed to analyse the handgrip positioning and the wedge effects on the backstroke start performance and technique. Ten swimmers completed randomly eight 15 m backstroke starts (four with hands on highest horizontal and four on vertical handgrip) performed with and without wedge. One surface and one underwater camera recorded kinematic data. Standardised mean difference (SMD) and 95% confidence intervals (CI) were used. Handgrip positioning did not affect kinematics with and without wedge use. Handgrips hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 20 publications
2
27
1
Order By: Relevance
“…This is not consistent with a proximal-to-distal order of joint extension. It remains unclear whether proximal-to-distal joint sequencing is optimal for backstroke starts, as some studies have found it to be associated with a shorter start time [3,16], while others have not [2,4]. However, in support of our second The Effects of Plyometric Warm-up on Lower Limb Muscle Activity and Time to 10m in the Backstroke Swimming Start hypothesis, we observed that longer head entry distances were strongly correlated with shorter times to 10 m.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…This is not consistent with a proximal-to-distal order of joint extension. It remains unclear whether proximal-to-distal joint sequencing is optimal for backstroke starts, as some studies have found it to be associated with a shorter start time [3,16], while others have not [2,4]. However, in support of our second The Effects of Plyometric Warm-up on Lower Limb Muscle Activity and Time to 10m in the Backstroke Swimming Start hypothesis, we observed that longer head entry distances were strongly correlated with shorter times to 10 m.…”
Section: Discussionsupporting
confidence: 62%
“…We observed differences in timing of hip and knee extensor activity between conditions. A proximal-to-distal recruitment of muscle activation and resulting order of joint extension benefits jumps [17,18] and backstroke starts [16]; however, it should be noted that this is not consistently observed [2,4]. In this study, peak gluteus maximus activity occurred before that of vastus lateralis in the control condition, but after the vastus lateralis in the plyometric warm-up condition based on a statistically significant p-value and a large effect size.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In 2014, the backstroke ledge was approved by FINA (Fédération internationale de natation, or International Swimming Federation) for use in competition. The backstroke ledge alters the angle as well as the coefficient of friction between the feet and the starting surface [1], fundamentally changing backstroke start performances [2][3][4]. Accordingly, findings from previous studies where the backstroke ledge was not used may no longer be relevant.…”
Section: Introductionmentioning
confidence: 99%